The Effects of Carbohydrate and Caffeine Mouth Rinsing on Arm Crank Time-Trial Performance - Sinclair, Jonathan; Bottoms, Lindsay (Journal of Sports Research, 2015)
This study aimed to determine whether carbohydrate (CHO) and caffeine (CAFF) mouth rinsing would improve 30 minute arm cranking time-trial performance. Twelve male participants (age 21.54 ± 1.28 years, height 179.46 ± 7.38 cm and mass 73.69 ± 5.40 kg) took part in the current investigation. Participants came to the laboratory on 3 occasions during which they performed 30 minute self-paced arm crank time trials. On one occasion water was given as a mouth rinse for 5 s (PLA), on another occasion a 6.4% CHO solution was given for 5 s and finally a 0.032% CAFF solution was given for 5s. Key measurements of distance covered, heart rate (HR), ratings of perceived exertion (RPE), cadence and power output were recorded throughout all trials. Distance covered during the CAFF (15.43 ± 3.27 km) and CHO (15.30 ± 3.31) mouth rinse trials were significantly (p<0.05) greater in comparison to PLA (13.15 ± 3.36 km). Cadence and power output and velocity were also significantly greater during the CAFF and CHO trials compared to PLA and CHO (p<0.05). No significant (P>0.05) differences between trials were observed for HR and RPE. CAFF and CHO mouth rinse serve to improve 30 minute arm cranking performance by mediating increasing cadence and power output without a concurrent increase in RPE and HR.